«Я відчуваю себе повноцінною частинкою великої Нації»: українська мова та самоідентифікація студентьської молоді. - Yaremko, Liliya; Levchuk, Pavel (Theoria et Historia Scientiarum, 2024)
The article, using the questionnaire method, presents and summarises theoretical issues of national identity and self-identification of student youth in the context of Russia’s war against Ukraine. The article traces the dynamic changes that have taken place in the minds of the younger generation: pride in speaking Ukrainian, a sense of being part of the Ukrainian nation, the formation of a selfsufficient political position of young people, and the positioning of themselves as part of their people in preserving the heritage of the Ukrainian nation (respectively, language, culture, history, traditions, etc.). There is a noticeable trend towards an increase in the number of young people who choose Ukrainian as their language of communication, and a greater use of Ukrainian content on social media. Young people eagerly learn other languages (in particular English, and Polish) in addition to Ukrainian in order to improve their language skills, communicate with foreigners in a wide range of ways, improve their professional skills, travel, translate books and articles, learn about the cultural values of other countries, and get information about Ukraine and events taking place in it.